(untitled) - Gude, Kathy (English, 2001)
A lively course for teenagers which focuses on language and skills training and introduces FCE exam-type tasks.
Keywords: Skills training,Đào tạo kỹ năng,Listening,Lắng nghe; Ability testing,Khả năng kiểm tra